The Influence of Business Intelligence to Maintain Customer Relationships in Small and Medium Enterprises in Indonesia - Muhammad Faisal Yul Zamrudi; Pungky Lela Saputri (Syntax Idea)
The adoption of Business intelligence (BI) has become increasingly prominent among organizations for attracting customers and gaining a competitive edge. This becomes even more important for small and medium enterprises (SMEs) which face immense pressure to retain existing customers and attract more customers for survival. This study presents a systematic literature review of studies investigating the impact of BI on customer relations with exclusive focus on Indonesia, which has a growing number of SMEs (also called ‘UMKMs’). By examining 15 papers published between 2013 to 2024, the findings of the study highlight that BI contributes to building better connections with customers and making them feel more engaged and satisfied. This study provides valuable insights for SMEs in Indonesia to adopt BI to attract more customers. The findings of the study also lay the foundation for future research, especially those wanting to perform an empirical investigation.